The User Interface Design of HIM Competencies Compliance Measurement Application Using Android Platform - Sari, P D L; ., Nuryati (KnE Social Sciences, 2018)
Background: According to Law on Ministry of Health 55/2013, Health Information Management (HIM), professionals as one kind of health practitioner shall maintain their professional standard and competencies. A review of the competencies is important to maintain the accountability of HIM. Re-evaluation with self-assessment method using manual questionnaire can be done. However, based on the interviews, there have been difficulties in data collection because of the limited time of HIM and the number of questionnaire. Objective: Designing the user interface of HIM competencies compliance measurement application using Android platform in accordance with the Google Material Design. Method: This design is using Lean User Experience method. Identify user needs by interview and FGD while validation is done by user testing method. Result: There are 14 main user interface design of HIM competencies compliance measurement. Those are: Splash Screen, Walkthrough, Forgot Password, Sign Up, Main Menu, Sub Unit, List Menu, Profil, Result and 3 Warning Screen. Keywords: interface design, competencies, HIM, android